Expectations of Mothers of Children With Cerebral Palsy Regarding Physical Therapy - Sajida Dilawar; Amna Yaseen; Reeta Mahesh; Muhammad Saad Khan (Journal of Modern Rehabilitation, 2020)
Introduction: This study aimed to find out the expectations of mothers of children with cerebral palsy (CP), who are engaged in rehabilitation programs, especially in physical therapy treatment. Materials and Methods: Clinical types and gross motor function levels of the children were documented. A questionnaire consisting of 6 open-ended questions was used to define the expectations and views of the mothers of CP children about the physiotherapy and rehabilitation programs for the children. A total of 100 mothers were interviewed through an observational study with six open-ended questions along with demographic data. Results: There was no significant agreement regarding the applied treatment methods and the appropriateness of the rehabilitation programs. Conclusion: The expectations of mothers of CP children are not as high as they wanted from rehabilitation according to their children’s needs.